A model based on endoscopic morphology of submucosal esophageal squamous cell carcinoma for determining risk of metastasis on lymph nodes - Zhuge, Lingdun; Wang, Shengfei; Xie, Juntao; Huang, Binhao; Zheng, Difan; Zheng, Shanbo; Mao, Hengyu; Pennathur, Arjun; Sanchez, Manuel Villa; Luketich, James D.; Xiang, Jiaqing; Chen, Haiquan; et al. (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Background: It is important to identify patients with esophageal squamous cell carcinoma (ESCC) in T1b stage that are the least likely to metastasize on the lymph nodes, to undergo endoscopic resection, especially for the patients unfit for esophagectomy. The relationship between endoscopic morphology and frequency of nodal metastasis has never been well studied. The aims of the study were to investigate the predictive value of endoscopic morphology for lymphatic metastasis, and to develop a risk stratification model in submucosal (T1b) ESCC. Methods: Pathologic variables of patients with T1b ESCC who underwent esophagectomy from 2006 through 2016 were collected and divided into training sets (patients between 2006 and 2011) and validation sets (patients between 2012 and 2016). The endoscopic morphology of the tumor was determined by analyzing endoscopic reports according to the Paris classification. The correlation between the clinicopathological factors and nodal metastasis was examined. A prediction model was developed to estimate the risk of metastasis using these predictors. Results: A total of 175 patients were included in this study. A tumor with an endoscopic shape of flat type (0–II type as Paris classification was defined) was significantly related to lower risk of lymphatic metastasis with the frequency of 15.5% (OR: 3.049, 95% CI: 1.363–6.819, P=0.005). The combination of endoscopic morphology with other pathologic characteristics including lymphovascular invasion, length of tumor, depth of tumor invasion into submucosa, and tumor differentiation improved the predictive value of the nodal metastasis. The risk stratification model was developed with a C-index of 0.726 (95% CI: 0.702–0.751), which identified a low risk subgroup with a lymph node rate of 7.2%. Conclusions: Our results suggest that when a tumor is in flat shape (0–II type) it is related to a less lymphatic metastasis, and the combination of the endoscopic morphology with the other four pathologic variables can yield a more robust approach to predict the risk of lymphatic metastasis in submucosal ESCC.